Pragmatik Bentang Alam Pedesaan (Studi Kasus Dusun Bendosari, Kec. Pujon, Kab. Malang) - Chairil Budiarto Amiuza; Yusfan A. Yusran; Lisa Dwi W.; Indyah Martiningrum (RUAS (Review of Urbanism and Architectural Studies), 2012)
Conditions and the potential for rural environments Bendosari, Pujon district, Malang, there seems to be a tendency lack balance Landscape Aesthetics and harmony of its. One effort to maintain balance and harmony preservation of the landscape, through the study of the rural landscape in the area. The method that used was a qualitative research method, through surveys and interviews to obtain visual and physical configurations and interrelationships landscape with functions in order for the village community. The interrelation of visual and physical organization of the natural environment and the rural built environments, arranged closely related to the physical, visual and physical follow natural visual dominated except in the village center. Functions for the visual and physical configurations that exist are the majority of the rural population, it is still natural and traditional, but most of the villagers are artificially centered and modern.Keywords: Pragmatics, Syntax, Landscapes aesthetic, Bendosari village